Human Resource Management Problems for Private Madrasah Aliyah Teachers in Regency - Nor Fitria; Istikomah (Universitas Muhammadiyah Sidoarjo, 2022)
Management is the process of utilizing all the resources owned by the organization to achieve the goals that have been set. management in a broad sense is planning, organizing, directing, and controlling organizational resources to achieve goals effectively and efficiently. The objectives of this study are to describe the problems of teacher human resource management at private madrasah aliyah in Sampang regency. This study uses a qualitative approach, which aims to explain the problem of human resource management for private Madrasah aliyah teachers, a qualitative approach is considered a research procedure that produces descriptive data in the form of words from observations, interviews and documentation. Data collection techniques by reviewing documents, interviews, and observations. It is analyzed through the following stages: data reduction, data presentation, and verification. The results of this study indicate that the problem with teacher human resources is that the number of teachers who teach is not in accordance with their academic qualifications because the management function of teacher human resources in madrasah aliyah does not run optimally starting from planning, management, procurement, procurement, development, assessment, control, compensation and dismissal. and the causes of the problem of teacher human resources are divided into two factors, namely internal factors, the character of teachers, lack of teacher innovation, lack of motivation and indifference to various changes, limited funds available while external causes such as Madrasah environmental conditions and conditions of socio-cultural development of the community, lack of continuous support from organization in teacher HR Management.